Nanocrystalline Cerium Dioxide Affects Erythrocyte Membrane State Under Blood Hypothermic Storage - Falko, Oksana; Kovalenko, Alina; Ovsiannikova, Tatyana; Klochkov, Vladimir; Chyzhevsky, Viktor (Problems of Cryobiology and Cryomedicine, 2023)
Here, we have studied the impact of nanocrystalline cerium dioxide (NCD) particles on erythrocyte membrane state in a model of hypothermic storage of blood samples by examining the content of lipid peroxidation (LPO) primary products and hematological indices (free and total hemoglobin, hematocrit and hemolysis levels). After hypothermic storage of blood samples within 5 weeks, no significant difference in hematological indices between the control and experimental groups was revealed. In 2 weeks of hypothermic storage, the cells from experimental group in NCD presence showed an increased content of mainly those primary LPO products, which precursors were polyunsaturated fatty acids with two double bonds (conjugated dienes and oxidienes), thereby indicating the free radical processes activation. Four weeks’ storage demonstrated significantly decreased content of all primary LPO products in the experimental group cells in contrast to the control group. To the final step of the study (5 weeks of storage), the content of all primary LPO products in experimental and control groups was similar, that was an evidence of the ability of NCD particles to affect the erythrocyte membrane as well change the LPO intensity depending on storage period. Probl Cryobiol Cryomed 2022; 32(4):267–276